Self-assembling antitumour prodrugs for localised drug delivery - Citossi, Francesca (2016)
Localised cancer therapy is a developing strategy used to overcome the systemic toxicity associated with intravenous systemic chemotherapy, which still represents the primary route of administration for the majority of current anticancer agents. Low molecular weight gelators (LMWGs) have recently gained increasing popularity as drug delivery platforms for localised cancer therapy: they are small molecules, which self-assemble into a 3D network via non-covalent interactions. Due to their inherent biocompatibility, LMWGs represent a viable alternative to the extensively explored polymer based drug delivery systems. One such drug delivery approach, based on LMWGs, involves the synthesis of gelator-based prodrugs of chemotherapeutic agents; however, to date, there remains a limited number of anticancer prodrugs that have gelation properties. Therefore, the present work aims to find new chemotherapeutic agents that display gelation properties by modification of the parent drug with known self-assembling groups. Two anticancer agents have been evaluated: the clinical antimetabolite methotrexate (MTX) and the experimental benzothiazole derivative 5F 203, both characterised by significant anticancer activity but systemic toxicity. Therefore, formulation of MTX and 5F 203 as LMWGs-based prodrugs for localised cancer therapy was considered a useful strategy to overcome the systemic toxicity of these antitumour drugs. Different synthetic approaches were explored to formulate self-assembling MTX prodrugs. The most successful one involved the synthesis of MTX derivatives bearing alkyl chains and aromatic groups at the α or both α and γ carboxylic acid terminals of MTX. Unfortunately, preliminary gelation tests performed on MTX acyl derivatives via a solvent-switch method, revealed lack of self-assembling properties. Therefore, the MTX conjugates developed were not suitable for localised drug delivery applications. Due to the absence of self-assembling properties of MTX conjugates, the potential gelation behaviour of novel derivatives of another anticancer candidate, the benzothiazole agent 5F 203, was considered, and two amide prodrugs series of 5F 203 were investigated. Amongst the compounds tested for gelation, 5F 203 succinic acid conjugate (68a) revealed formation of a hydrogel at physiological pH. Rheological measurements confirmed its LMWG nature, showing formation of a cross-linked gel network. In vitro growth inhibitory assays against breast (MCF-7) and ovarian (IGROV-1 and OVCAR-4) carcinoma cell lines showed overall activity of 5F 203 amide prodrugs in inhibiting cell proliferation. Release studies from the gel matrix of 68a revealed a release of the derivative and the active drug over 3 days, thus confirming its potential application as a depot formulation for localised delivery of 5F 203. In order to improve the rate of conversion of prodrugs into the parent amine 5F 203, compared to the previous amide series developed, acyloxyalkoxycarbonyl derivatives of 5F 203 were synthesised. Gelation tests displayed self-assembling behaviour for derivatives 76a-76c and rheological studies confirmed the LMWG nature of the new entities. The acyloxyalkoxycarbonyl prodrugs revealed in vitro potencies similar to those displayed by 5F 203, when tested against MCF-7 and IGROV-1 cell lines. The isobutyl carbamate prodrug (76a) proved to be the most potent of the series, showing hydrolysis into the active drug 5F 203, when incubated in either PBS buffer, rat or human plasma; release from the gel matrix also showed release of 5F 203 in PBS within 72 h. The outcomes from this work have therefore provided a basis for future optimisation and development of LMWG derivatives of 5F 203, as depot formulations for localised delivery of this anticancer agent.